Comparison of freeze-thaw and sonication cycle-based methods for extracting AMR-associated metabolites from Staphylococcus aureus - Singh, Rita; Thakur, Lovnish; Kumar, Ashok; Singh, Sevaram; Kumar, Shailesh; Kumar, Manoj; Kumar, Yashwant; Kumar, Niraj (Frontiers in Microbiology, 2023)
Emerging antimicrobial resistance (AMR) among Gram-positive pathogens, specifically Staphylococcus aureus, is becoming a leading public health concern demanding effective therapeutics. Metabolite modulation can improve the efficacy of existing antibiotics and facilitate the development of effective therapeutics. However, it remained unexplored for S. aureus primarily due to the dearth of optimal protocols, including for extracting AMR-associated metabolites. Therefore, in this investigation, we have compared the performance of the two most widely used methods, i.e., freeze-thaw cycle (FTC) and sonication cycle (SC), alone and in combination (FTC+SC), and identified the optimal method for this purpose. A total of 116, 119, and 99 metabolites were identified using the FTC, SC, and FTC + SC methods respectively leading to identification of 163 metabolites cumulatively. Out of 163, 69 metabolites were found to be associated with AMR in published literature consisting of the highest number of metabolites identified by FTC (57) followed by SC (54) and FTC+SC (40). Thus, the performances of FTC and SC methods were comparable with no additional benefits of combining both. Moreover, each method showed biasness towards specific metabolite(s) or class of metabolites suggesting that choice of metabolite extraction method shall be decided based on the metabolites of interest in the investigation